Intranasal dexmedetomidine improves postoperative sleep quality in older patients with chronic insomnia: a randomized double-blind controlled trial - Wu, Jinghan; Liu, Xingyang; Ye, Chunyan; Hu, Jiajia; Ma, Daqing; Wang, E. (Frontiers in Pharmacology, 2023)
Objective: This study was determined to investigate the impact of intranasal dexmedetomidine on postoperative sleep quality in older patients with chronic insomnia during their hospitalization after surgery. Design: A randomized double-blind controlled trial. Registration number: ChiCTR2200057133 (http://www.chictr.org.cn/). Setting and Participants: The study was carried out at Xiangya Hospital, Central South University. 110 participants with chronic insomnia were analyzed. Methods: This trial enrolled older patients who underwent total hip/knee arthroplasty and randomized them to receive intranasal dexmedetomidine (2.0μg/kg) or saline daily at around 9 pm after surgery until discharge. The primary outcomes were subjective sleep quality assessed with the Leeds Sleep Evaluation Questionnaire (LSEQ). The secondary outcomes included the objective sleep quality measured with the Acti-graph, the Pittsburgh Sleep Quality Index (PSQI), the Insomnia Severity Index (ISI), The other outcomes included the incidence of delirium, levels of inflammatory factors, visual analog scale (VAS) pain scores, postoperative opioid consumption, and treatment-related adverse events. Results: 174 patients were screened for eligibility, and 110 were recruited and analyzed. The DEX group had significantly higher scores on both the LSEQ-Getting to sleep and LSEQ-Quality of Sleep at each time point compared to the placebo (P<0.0001), The least squares (LS) mean difference in LSEQ-GTS score at T0 between placebo group and DEX group was 2 (95% CI, -1 to 6), p=0.4071 and at T5 was -14 (95% CI, -17 to -10), p <0.0001; The LS mean difference in the LSEQ-QOS score at T0 was -1 (95% CI, -4 to 1), p=0.4821 and at T5 was -16 (95% CI, -21 to -10), p <0.0001. The DEX group exhibited significant improvement in Total Sleep Time (TST), Sleep Onset Latency (SOL), and Sleep Efficiency (SE), at each time point after treatment compared to the placebo group (P<0.0001). The PSQI and ISI scores in the DEX group were reduced after treatment (P<0.001). No significant adverse events were reported with the use of dexmedetomidine. Conclusions and Implications: This study demonstrates that intranasal administration of dexmedetomidine improves postoperative sleep quality in older patients with chronic insomnia who undergo surgery, without increasing the incidence of adverse effects.